2008
DOI: 10.1165/rcmb.2007-0299oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-6 in Bleomycin-Induced Lung Inflammatory Changes in Mice

Abstract: Interleukin-6 (IL-6) is known to be involved in the pathogenesis of various inflammatory diseases, but its role in bleomycin (BLM)-induced lung injury and subsequent fibrotic changes remains to be determined. We evaluated the role of IL-6 in the lung inflammatory changes induced by BLM using wild-type (WT) and IL-6-deficient (IL-6(-/-)) mice. The mice were treated intratracheally with 1 mg/kg BLM and killed 2, 7, or 21 days later. Lung Inflammation in the acute phase (Days 2 and 7) was assessed by differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(164 citation statements)
references
References 35 publications
9
150
2
3
Order By: Relevance
“…6 of activation due to the absence of E-cadherin shedding. mRNA levels for TGF-␤1 did not differ between genotypes, but mRNA for connective tissue growth factor and IL-6, which are profibrotic in this model, [45][46][47][48][49] were significantly higher in CD103 Ϫ/Ϫ lung tissues than in wild-type lungs, consistent with the marked increase in pulmonary fibrosis in seen CD103…”
Section: E-cadherin-cd103 Interactions Alter DC Cytokine Productionsupporting
confidence: 73%
“…6 of activation due to the absence of E-cadherin shedding. mRNA levels for TGF-␤1 did not differ between genotypes, but mRNA for connective tissue growth factor and IL-6, which are profibrotic in this model, [45][46][47][48][49] were significantly higher in CD103 Ϫ/Ϫ lung tissues than in wild-type lungs, consistent with the marked increase in pulmonary fibrosis in seen CD103…”
Section: E-cadherin-cd103 Interactions Alter DC Cytokine Productionsupporting
confidence: 73%
“…High IL-6 levels are correlated with alveolar hypercellularity and neutrophil counts in IPF [28]. Recently, IL-6-deficient mice demonstrated attenuation in bleomycin-induced lung injury and fibrosis [29]. Therefore, one of the mechanisms for the inhibition of inflammation and fibrosis by ONO-4057 may be associated with the decrease in IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent publications have shown that Mfge8-independent apoptotic cell clearance induces phagocyte release of IL-1β and IL-6 (43,44), cytokines that induce inflammation and fibrosis (45,46). Conversely, Mfge8-dependent apoptotic cell clearance has been shown to induce the release of TGF-β, a profibrotic and antiinflammatory cytokine (32,44).…”
Section: Figurementioning
confidence: 99%